2020
DOI: 10.1088/1361-648x/ab6d8f
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study on photovoltaic properties of 2D Cs2PbI4-black phosphorus heterojunctions

Abstract: Both 2D perovskite Cs 2 PbI 4 and phosphorus are significant optoelectronic semiconductor materials, the optical-electrical characters between both contact interfaces are interesting topics. In present work, we demonstrate comparative investigation of optoelectronic properties for two kinds of electrical contact interfaces. i.e. Pb-I and Cs-I interfaces with black phosphorus contacts. The carrier transport, charge transferring and optical properties for both cases are investigated by using first principle calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…In order to nd out the effect of halogen elements on Cs 46,47 With the halogen varying from Cl to I, the interface binding energies of Cs 2 PbX 4 -PtSe 2 heterostructures decrease rapidly and heterostructures become more stable in energy due to the lower interface binding energy. 48,49 .02 eV, and 1.29 eV, which approach optimal bandgap (1.34 eV) for solar cells. 54 Furthermore, the Mott-Wannier theory has been used to approximate exciton binding energies in 2D.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…In order to nd out the effect of halogen elements on Cs 46,47 With the halogen varying from Cl to I, the interface binding energies of Cs 2 PbX 4 -PtSe 2 heterostructures decrease rapidly and heterostructures become more stable in energy due to the lower interface binding energy. 48,49 .02 eV, and 1.29 eV, which approach optimal bandgap (1.34 eV) for solar cells. 54 Furthermore, the Mott-Wannier theory has been used to approximate exciton binding energies in 2D.…”
Section: Resultsmentioning
confidence: 89%
“… 46,47 With the halogen varying from Cl to I, the interface binding energies of Cs 2 PbX 4 –PtSe 2 heterostructures decrease rapidly and heterostructures become more stable in energy due to the lower interface binding energy. 48,49 Above all, the interlayer distance ranging from 2.76 Å to 2.91 Å belong to vdW and small interface binding energy revealed that 2D Cs 2 PbX 4 –PtSe 2 heterostructures are formed by vdW contact. The lattice mismatches of the 2D Cs 2 PbCl 4 –PtSe 2 , Cs 2 PbBr 4 –PtSe 2 and Cs 2 PbI 4 –PtSe 2 heterostructures in the a and b directions are less than 7.25%, 4.86% and 5.54%.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations